'21st Century Welfare' in Historical Perspective: Disciplinary Welfare in the Depression of the 1930s and Its Implications for Today. (June 2021) - Cooper, Matthew
Since 2010, UK governments have intensified conditionality as part of a programme of 'welfare reform'. Social scientists have undertaken much critical analysis but less attention has been paid to possible historical parallels. This article sheds new light on welfare reform through comparison with the depression of the 1930s. It undertakes a documentary analysis of policy in the 1930s informed by a governmentality perspective. In both periods, governments committed to liberal orthodoxies and feared the unemployed would become vulnerable to 'demoralization' and 'dependency'; their behaviour and character were determinant of their rights to support. However, there are notable differences in what interventions have been considered appropriate. The article assesses the significance of continuities and contrasts, and argues in particular that the severity and ubiquity of behavioural regulation employed today is even greater than that seen in the 'dark decade' of the great depression.